Iot Monitoring System For Smart Agriculture - Dr Chirra Kesava Reddy, Merigila Kishore Babu, Dr.D.V.Divakara Rao, Ranjan Walia, Rajeev Sharma, Shyam Kumar Katta (Drugs and Cell Therapies in Hematology, 2021)
To smart farming, the Internet of Things (IoT) becomes critical. While IoT sensors could provide data on their farmlands, smart agriculture is a modern phenomenon. An objective of this proposal is to use emerging technologies, such as the Internet of Things (IoT) and smart farming using computerization. Atmospheric elements must be closely monitored in enhancing the production of effective cultivations. Continued surveillance of temperature and relative humidity in farmlands using sensors based on the CZC3160 unique chip is a characteristic of this article. This camera is connected to the CZC3160, which takes photos and sends them through MMS to the owners’ smartphone through wireless